2015
DOI: 10.1097/fpc.0000000000000108
|View full text |Cite
|
Sign up to set email alerts
|

Poor warfarin dose prediction with pharmacogenetic algorithms that exclude genotypes important for African Americans

Abstract: Objectives Recent clinical trial data cast doubt on the utility of genotype-guided warfarin dosing, specifically showing worse dosing with a pharmacogenetic versus clinical dosing algorithm in African Americans. However, many genotypes important in African Americans were not accounted for. We aimed to determine if omission of the CYP2C9*5, *6, *8, *11 alleles and rs12777823 G>A genotype affects performance of dosing algorithms in African Americans. Methods In a cohort of 274 warfarin-treated African American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 37 publications
2
70
0
Order By: Relevance
“…This could explain the overdosing observed among African Americans receiving genotype-guided dosing in COAG. This has been highlighted by a recent study by Drozda et al, 35 which showed that the algorithm used in COAG overestimates warfarin doses in African Americans possessing CYP2C9 (*5, *6, *8, and *11) variants. Our findings are consistent with this.…”
Section: 14mentioning
confidence: 86%
“…This could explain the overdosing observed among African Americans receiving genotype-guided dosing in COAG. This has been highlighted by a recent study by Drozda et al, 35 which showed that the algorithm used in COAG overestimates warfarin doses in African Americans possessing CYP2C9 (*5, *6, *8, and *11) variants. Our findings are consistent with this.…”
Section: 14mentioning
confidence: 86%
“…Genetic variants that influence drug response may occur exclusively or at different frequencies between population groups. 28, 29 However, in a recent review of the pharmacogenomics of ICS response, 30 none of the existing genome-wide association studies included substantial numbers of African American individuals. Therefore, it is not known whether the risk variants that have been identified to date are generalizable to multiple population groups.…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to make meaningful comparisons among Asian participants due to an inadequate sample size (n=18). Sixth, the COAG trial did not include genetic variants that might uniquely improve dose prediction in black populations [18,20,21]. …”
Section: Discussionmentioning
confidence: 99%